Implementation of Counseling Guidance for Children with Special Needs (Viewed from Psychological Aspects, Socio-Culture and Science and Technology Development) - Mareza, Lia; Nugroho, Agung (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The purpose of this study is to provide an overview of the importance of implementing counseling for children with special needs with auditory barriers in terms of psychological, socio-cultural aspects to the development of science and technology. The role of guidance and counseling services in the realm of education becomes a basic necessity to support the growth and development of students optimally, starting from personality development, social skills (activity daily) to developments related to the potential of students so that they are expected to achieve their actualization later The research method used is descriptive qualitative research, by describing the implementation of counseling in the school, through observation, interviews, and documentation. The results of this study are counseling becomes a primary need for children with special needs, this is because of several aspects such as psychological or emotional instability than the ability to socialize in society such as the influence of bullying or pressure social, to the ability of children with special needs to keep up with as a form of interaction from cyberspace or the use of advanced technology. The implication of this study is that counseling is actually the basic foundation for research in children with special needs that are useful as identification of potential and talent as well as an effort to solve problems that occur for children with special needs